1982
DOI: 10.1017/s0033291700043270
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Tolerance Test: human growth hormone response and insulin resistance in primary unipolar depressed, bipolar depressed and control subjects

Abstract: SynopsisPreliminary data from the National Institute of Mental Health – Clinical Research Branch Collaborative Program on the Psychobiology of Depression dealing with the human growth hormone (hGH) response to the Insulin Tolerance Test (ITT) during the pre-treatment (drug-free) period of the study are presented in this paper. Data are reported for 54 unipolar depressed, 21 bipolar depressed, and 40 normal control subjects, who represent approximately 50% of the final subject sample to be studied. In this popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
1

Year Published

1983
1983
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 26 publications
2
11
0
1
Order By: Relevance
“…Our findings parallel a series of studies in the adult literature that have found links between depressive disorders or severity of depressive symptoms and decreased insulin sensitivity in women and men (3, 6–8, 11). Despite meal‐level sex differences in depressive symptoms and insulin resistance, the observed relationship between depression and insulin was not significantly different among adolescent boys and girls.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our findings parallel a series of studies in the adult literature that have found links between depressive disorders or severity of depressive symptoms and decreased insulin sensitivity in women and men (3, 6–8, 11). Despite meal‐level sex differences in depressive symptoms and insulin resistance, the observed relationship between depression and insulin was not significantly different among adolescent boys and girls.…”
Section: Discussionsupporting
confidence: 86%
“…Overweight youth have decreased insulin sensitivity compared to their non‐overweight counterparts, placing them at heightened risk for negative health consequences including type 2 diabetes (2). However, evidence from adult studies suggests that psychological factors may also affect insulin sensitivity (3–11). In overweight and non‐overweight adults, sub‐clinical and clinical threshold depressive symptoms are correlates of, and potential risk factors for, the development of decreased insulin sensitivity (3, 6–10), type 2 diabetes (5, 12, 13), and other aspects of the metabolic syndrome (4, 11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Data from subjects in whom base line GH plasma concentrations exceeded 5 ng/ml were excluded from evaluation according to Catt [1970] and Koslow et al [1982], Maximum PRL responses and maximum GH responses were compared using Student's t test for unpaired data or Mann-Whitney U test, if appropriate. NA, cortisol and VAS responses of patients and controls were compared at indicated time points by Student's t test for unpaired data or Mann-Whitney U test, respectively.…”
Section: Statistical Evaluationmentioning
confidence: 99%
“…The correlation between depressive symptoms and metabolic syndrome is slightly higher in monozygotic twins than dizygotic twins, suggesting that genetics play a critical role in both disorders (McCaffery et al, 2003). Resistance to insulin, which is a risk factor for developing metabolic syndrome, is a common occurrence in depressed patients (Koslow et al, 1982;Okamura et al, 2000;Winokur et al, 1988), which suggests that insulin links depression with metabolic syndrome. Insulin exerts dosedependent effects on food intake and energy regulation.…”
Section: Metabolic Alterationsmentioning
confidence: 99%